Therapeutic hypnosis with children and adolescents - Sugarman, Laurence I.; Wester, William C., II (William Carl), 1939- (Bancyfelin, Carmarthen, Wales, UK : Crown House Publishing Limited, 2014)
This text examines the wide-ranging applications and promise of the use of hypnosis with children. The book develops core principles of clinical hypnosis with children and adolescents and each contributor delineates how they apply these precepts in a range of psychological and medical settings. The result is a constellation of perspectives and clinical applications that move the reader beyond literature review to practical advice. In Part 1 the broad framework of hypnosis with children is elucidated: concepts, developmental considerations, approaches to induction, hypnotic ability, hypnosis with families and ethical considerations are reviewed. Additionally, the implications of a developmental perspective in hypnosis are extrapolated to work with adults. Parts 2 and 3 illuminate key psychological and medical applications of hypnosis. In the psychological realm, trauma, habit disorders, somatoform disorders, depression, anxiety and behavioural disorders are scrutinized. A particularly original chapter explores the use of clinical hypnosis with the family as the patient. The medical section describes the integration of hypnosis from acute care settings to the operating room; in pain management, chronic diseases, elimination disorders, recurrent pain and palliative care. Throughout the book, clinical vignettes draw the reader into the hypnotic encounter while supportive evidence, strategies and caveats provide insights.
Previous edition: 2007.
Includes bibliographical references and indexes.
Keywords: Hypnosis; Adolescent; Child